The religious origins of the French Revolution : from Calvin to the civil constitution, 1560-1791 - Van Kley, Dale K., 1941- (Yale University Press, 1996)
Although the French Revolution is associated with efforts to dechristianize the French state and citizenry, it actually had long-term religious - even Christian - origins, claims Dale Van Kley in this controversial new book. Looking back at the two and a half centuries that preceded the revolution, Van Kley explores the diverse, often warring religious strands that influenced political events up to the revolution.